2004
DOI: 10.1021/es030568i
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Evidence for a Naturally Produced, Bioaccumulating Halogenated Organic Compound

Abstract: Halogenated organic compounds (HOCs) such as 1,1'-dimethyl-3,3',4,4'-tetrabromo-5,5'-dichloro-2,2'-bipyrrole (DBP-Br4Cl2) and heptachloro-1'-methyl-1,2'-bipyrrole (Q1) have been detected worldwide, sometimes at high levels in Antarctic air, seabird eggs, the blubber of marine mammals, and, most notably, even human milk. To date, it has been difficult to determine whether these compounds are natural products or derived from industrial synthesis. Molecular-level 14C analysis of these compounds is particularly ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…It has been suggested previously that bioaccumulated bipyrroles are produced naturally (Reddy et al, 2004;Wu et al, 2002). The presence of radiocarbon in one bioaccumulated DMBP implies, at least in part, a biogenic origin (Reddy et al, 2004).…”
Section: Origin and Distributionmentioning
confidence: 87%
See 2 more Smart Citations
“…It has been suggested previously that bioaccumulated bipyrroles are produced naturally (Reddy et al, 2004;Wu et al, 2002). The presence of radiocarbon in one bioaccumulated DMBP implies, at least in part, a biogenic origin (Reddy et al, 2004).…”
Section: Origin and Distributionmentioning
confidence: 87%
“…The presence of radiocarbon in one bioaccumulated DMBP implies, at least in part, a biogenic origin (Reddy et al, 2004). Additionally, a structurally similar hexabrominated 2,2'-bipyrrole is a known marine bacterial metabolite (Andersen et al, 1974).…”
Section: Origin and Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional benefit of this approach is that the absolute amount of 14 C in natural products may vary slightly depending on the type of organism that synthesized them, and also when and where the organism grew. To obtain some baseline data, Reddy et al (2004) isolated 2, 4-dibromophenol (2, 4-DBP) and 2, 3, 4-tribromopyrrole (2, 3, 4-TBP) from Saccoglossus bromophenolosus and S. kowalevskii, respectively. These saccoglossoids were selected because they are easily sampled, and these compounds because significant research has been performed on their biosynthesis, chemical ecology and biogeochemistry (Higa et al 1980, Fielman & Targett 1995, King et al 1995, Woodin et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…These saccoglossoids were selected because they are easily sampled, and these compounds because significant research has been performed on their biosynthesis, chemical ecology and biogeochemistry (Higa et al 1980, Fielman & Targett 1995, King et al 1995, Woodin et al 1997. Reddy et al (2004) found that both compounds were natural as they contained detectable levels of 14 C (and hence were not from a petrogenic source). The actual 14 C values were more depleted (Δ 14 C = -170 ‰ for 2, 4-DBP and -130 ‰ for 2, 3, 4-TBP) than recently fixed carbon, which for coastal and open ocean surface waters is > 0 ‰ (Fig.…”
Section: Introductionmentioning
confidence: 99%